Patients’ level of satisfaction on quality of health care at Mwananyamala hospital in Dar es Salaam, Tanzania - Khamis, Kudra; Njau, Bernard (BMC health services research, 2014)
Background Enhancing quality of health care delivered in public health facilities in developing countries is a key prerequisite to increase utilization and sustainability of health care services in the population. The aim of the study was to determine patients’ level of satisfaction on the quality of health care delivered at the out-patient department (OPD) in Mwananyamala hospital in Dar es Salaam, Tanzania. Methods A cross-sectional study design was conducted from April to May, 2012. A systematic sampling method was employed to select 422 study subjects. A pre-tested SERVQUAL questionnaire was used to collect data and one-sample t-test was employed to identify patients’ level of satisfaction and principal component analysis to identify key items that measure quality of care. Results Patients’ level of satisfaction mean gap score was (-2.88 ± 3.1) indicating overall dissatisfaction with the quality of care. The level of dissatisfaction in the five service dimensions were as follows: assurance (-0.47), reliability (-0.49), tangible (-0.52), empathy (-0.55), and responsiveness (-0.72). Conclusion Patients attending OPD at Mwananyamala hospital demonstrates an overall dissatisfaction on quality of care. Hospital management should focus on: improvement on communication skills among OPD staff in showing compassion, politeness and active listening, ensure availability of essential drugs, and improvement on clinicians’ prescription skills.